Diseño de un manual de procesos para control de inventarios para la Empresa Pública La Nacional de Loja EP. Ciudad de Loja. Periodo 2024 - Pullaguari Pineda, Ruth M. (2024)
This curricular integration project has been designed under the premise that every enterprise requires effective control and management of its inventory. The company currently analyzed, lacks a control system that allow its employees to have clear guidance on the activities necessary during the processes of receiving, storing, and distributing goods. Consequently, the company often finds itself compelled to make hasty decisions that can jeopardize its profitability. Based on these considerations, the aim of this research is to develop a Process Manual for Inventory Control at La Nacional de Loja Public Enterprise. This manual seeks to provide efficient and effective management in this critical area, offering employees a practical and comprehensible tool that facilitates everyday activities.Additionally, there is a need to equip the management team with a robust system that ensures constant control and adequate supervision. To achieve this objective, the study employs both deductive and inductive approaches aimed at deriving logical conclusions based on the data collected during the research. These methods facilitate the comparison of the obtained results with findings from similar prior studies. The presented process manual intends to address and rectify the existing deficiencies within the company, relying on the principles of sound inventory management. The goal is to design an organizational system that fosters respect and collaboration among employees, thereby enabling the company to effectively achieve its objectives.